(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2026)
This study aims to carbonise water hyacinth, activate it chemically using ZnCl₂, and apply the resulting material in textile finishing to enhance selected properties of clothing. Water hyacinth, a widely occurring free-floating perennial aquatic weed, is often regarded as invasive; its conversion into a value-added textile finish therefore presents both environmental and functional benefits. The carbonisation process produces concave, oval-shaped carbon nanoparticles measuring approximately 200 nm by 100 nm, which are subsequently applied to fabrics using padding, coating, coat–pad curing, and infrared dyeing techniques. Among these, the coated samples produced through multiple padding cycles exhibit the most promising performance in terms of FTIR characteristics, air permeability, and stiffness. Although the treatment does not significantly improve mechanical properties such as tensile, bursting, or tear strength, it does enhance thermal behaviour, yielding a 13.8% increase in thermal insulation (CLO) and a 14.3% increase in thermal resistance (m²·K/W). Notably, the treated samples also demonstrate 100% odour resistance. Energy Dispersive Spectroscopy confirms the material composition, showing 99.32% carbon and 0.32% zinc distributed uniformly across the examined areas, indicating successful particle deposition.